2021
DOI: 10.5334/pb.1057
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Comprehensive Understanding of Body Image: Integrating Positive Body Image, Embodiment and Self-Compassion

Abstract: Body image (BI) disturbance is a relevant factor in the etiology and treatment of eating disorders (ED). Although progress has been made in recent decades in understanding BI and its relationship with ED, the efficacy of BI disturbance prevention and intervention programs is still limited. In order to reach deeper understanding of BI disturbance and clarify the interactions between some protective and risk factors related to this construct, we carried out a literature review on some specific BI-related factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 123 publications
(125 reference statements)
2
16
0
Order By: Relevance
“…Our correlation analysis found that the self-compassion of young BCS was directly and negatively associated with BID, which supported the hypothesis H1. This result con rms previous studies' ndings regarding the association of increasing self-compassion with less BID [11,13,37]. Young BCS view changes in their appearance and function as a part of their suffering.…”
Section: Self-compassion Negatively Related To Bidsupporting
confidence: 89%
See 2 more Smart Citations
“…Our correlation analysis found that the self-compassion of young BCS was directly and negatively associated with BID, which supported the hypothesis H1. This result con rms previous studies' ndings regarding the association of increasing self-compassion with less BID [11,13,37]. Young BCS view changes in their appearance and function as a part of their suffering.…”
Section: Self-compassion Negatively Related To Bidsupporting
confidence: 89%
“…For example, BCS are more likely to avoid situations that highlight aspects of their physical appearance in order to protect themselves from embarrassment and low self-esteem [22]. Although these coping styles can help individuals alleviate their negative emotions in the short term, in the long run, they can lead to dysfunction, making these individuals addicted to pain and failure, which aggravated their BID and associated psychological distress [24,37,39]. Germer et al [40] showed that training in self-compassion can reduce maladaptive coping and psychological distress.…”
Section: The Mediation Effects Of Avoidance and Acceptance-resignatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have recently shifted toward exploring positive body image in addition to negative body image, particularly within the contexts of prevention and treatment ( 1 , 2 ). Effective treatments have the potential to prevent the psychological distress associated with negative body image; however, research supporting the efficacy of various treatments in college-aged women is limited ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that vaccinations are a health preventive measure designed to protect the physical body [13], willingness to be vaccinated may also be related to people's thoughts about, attitudes to, and perceptions of their body [14]. Previous studies have found that positive body-image attitudes reflecting body appreciation (i.e., acceptance, respect, protection, and love towards one's body), were associated with individuals' health-protective behaviors, including screening for cancer, sun protection, limiting amount of alcohol use, engagement in healthy eating practices, exercise frequency, the pursuit of medical attention when required, engagement in meditation, and use of appropriate oral health and sexual health behaviors [15][16][17].…”
Section: Introductionmentioning
confidence: 99%